2017
DOI: 10.1159/000479317
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Estradiol and Several Lifestyle Factors, but Not <b><i>Helicobacter pylori</i></b> Infection, Are Significant Risks for Osteopenia in Japanese Females

Abstract: Background: The primary cause of osteoporosis in women is increased bone resorption and decreased bone density associated with reduced estrogen secretion. Several studies have demonstrated a relationship between Helicobacter pylori infection and osteoporosis regardless of estrogen levels. This study examined the relationship between H. pylori infection and osteopenia together with estrogen levels, calcium intake, and several lifestyle factors. Methods: This study included 473 healthy women who underwent a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…It is clear that the primary cause of osteoporosis in women is increased bone resorption and decreased bone density as a result of decreased estrogen secretion (Chinda et al, 2017; Khosla, Atkinson, Melton, & Riggs, 1997; Zebaze et al, 2010). Meanwhile, testosterone aromatizes to estradiol in men as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the primary cause of osteoporosis in women is increased bone resorption and decreased bone density as a result of decreased estrogen secretion (Chinda et al, 2017; Khosla, Atkinson, Melton, & Riggs, 1997; Zebaze et al, 2010). Meanwhile, testosterone aromatizes to estradiol in men as well.…”
mentioning
confidence: 99%
“…In Japan, many women without symptoms are found to have reduced bone mass during medical examinations and the start of treatment. However, no such medical examinations are performed for men, who are often diagnosed as having osteoporosis only after a fracture (Orimo et al, 2012).It is clear that the primary cause of osteoporosis in women is increased bone resorption and decreased bone density as a result of decreased estrogen secretion (Chinda et al, 2017;Khosla, Atkinson, Melton, & Riggs, 1997;Zebaze et al, 2010). Meanwhile, testosterone aromatizes to estradiol in men as well.…”
mentioning
confidence: 99%
“…Vitamin D deficiency reduces the carboxylation of osteocalcin and reduces the BMC of the total body and the lumbar spine [167]. It is noteworthy that many peri-pubertal healthy adolescents have subclinical deficiency of vitamin D [105,168-170] and vitamin K2 [167,171,172]. This may be attributable to the high bone turnover in children [105,172] and the fat-restricted diet that is commonly enforced by the parents, given the fact that both vitamin D and K2 are fat-soluble vitamins.…”
Section: The Role Of Vitamin D In the Etiopathogenesis Of Adolescent mentioning
confidence: 99%
“…Shih-Chun Lin conducted a retrospective study including 365 women and showed that H. pylori is related to osteoporosis in females [ 27 ], while others think that there is no correlation between them in females. Daisuke Chinda conducted a study of 473 healthy women and found that H. pylori is not a significant risk factor for osteopenia [ 28 ]. In our study, we analysed the relationship between H. pylori infection and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%